A COMPARATIVE STUDY OF THE INDIAN PRIMARY MARKET'S "POOLING OF RESOURCES IN THE STOCK & CORPORATE BOND MARKET" - N.D., Nalini; Vittala, K.R. Pundareeka (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The Indian capital market is well-organized and has a solid base. As a result, investors from all over the world are now keenly monitoring the Indian stock market. The majority of funding in India is provided by bank lending, with the remainder coming from the equity market. The bond market has a huge impact on the formation of initiatives in India as an alternative source of funding. This article analyses the effect of the public offering of equities on the corporate bond market in order to compare the volume of issuance and the value of the money pooled from the primary stock market and the corporate bond market year over year. Data for the study obtained from Hand book on Indian capital market published by SEBI for the period of 2010 – 2022 Descriptive statistics, Paired t test, regression test is used for the analysis & outcome of the study is 81% of CD market offering can be projected from primary equity market offering, corporate bond market financing rose by 147% YOY, whereas under primary equity market declined by 30%. Raising interest rate, volatility in the capital market are the major reason for such difference. Variance in the corporate bond market subscription comparatively higher than equity market which is 1184%, on the other hand it is 157% in equity market.